What motivates Generation Z in the multi-generational workplace? Insights into the motivation drivers of Generation Z employees at Crest - Fewings, Fionah Sibongile (2019)
For the first time in history, up to five generations of employees, young and old will be working by side by side. The latest generation currently joining the workforce is called Generation Z. Posited to be the most ‘truly global generation’ that will instigate the vastest generational shift in the workplace (Tulgan, 2013), the need to understand this cohort is great. This study seeks to examine the motivation drivers of Generation Z in the multi-generational workplace, in order to understand how better to attract, retain and engage this group into the multi-generational workforce. A mixed methods research approach was conducted with analysis of annual employee survey (2017 to 2018) combined with interviews of current Gen Z associates. The findings show that there are no significant differences across the generations in the indicators of engagement survey. A closer examination into the motivation drivers of Gen Z revealed that opportunities of advancement, the nature of the job and promotions are key motivating factors for Gen Z employees at Crest. The implications of this study are considered along with a number of recommendations being made based on the findings.